THE ROLE OF PROCESS OPTIMIZATION IN MODERN BUSINESS EDUCATION-BRIDGING THE GAP BETWEEN THEORY AND PRACTICE (NAU Journal of Technology and Vocational Education, 2025)
This study aimed at examining the role of process optimization in modern business education-bridging the gap between theory and practice. The study employed descriptive research design to study a population of 554 of business studies teachers in secondary schools in Awka South Local Government Area. Random sampling technique was employed to select 21 business studies teachers from 4 selected secondary schools. This gave a total of 84 business studies teachers. Structured questionnaire was used for data collection from the respondents. Mean statistics was employed to analyze the data collected. 2.5. point was set for accepting the mean. The findings of the study indicated that process optimization in business education programme is important on the areas of curriculum improvement by incorporating microelectronics, telecommunication equipment, internet and computers, Canvas, Zoom, Blackboard, Moodle and Microsoft Teams applications into business education curriculum. The study concluded that process optimization is needed to improve the efficiency and effectiveness of business education programme imparting the required skills, competence, knowledge and attitudes on students to be able to cope in the present-day technology labour market. Hence, the study recommended that there should be optimization and restructuring of business education curriculum include artificial intelligence, Canvas, Zoom, Blackboard, Moodle and Microsoft Teams technologies to enhance e-virtual teaching and students’ acquisition of employability skills.
Keywords: Role; optimization; process; modern; business; education